1997
DOI: 10.1101/gad.11.10.1277
|View full text |Cite
|
Sign up to set email alerts
|

A novel Mcm1-dependent element in the SWI4, CLN3, CDC6, and CDC47 promoters activates M/G1-specific transcription.

Abstract: We have identified a novel promoter element that confers M/Gl-specific transcription in Saccharomyces cerevisiae. This element, which we call an ECB (early cell cycle box), was first identified in the SWI4 promoter, but it is also present in the promoter of a G 1 cyclin CLN3, as well as in the promoters of three DNA replication genes: CDC6, CDC47, and CDC46. Transcripts from all five of these genes oscillate during the cell cycle and peak at the M/G1 boundary, as do isolated ECB elements in reporter constructs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
183
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(193 citation statements)
references
References 62 publications
(81 reference statements)
10
183
0
Order By: Relevance
“…This cluster has similarities to the CLB2 cluster, except that peak expression is slightly later. Searches of the upstream regions reveal that the majority of these genes contain binding sites for Mcm1p, as was previously shown for some members of the cluster (McInerny et al, 1997). Some, but not all, of these MCM1 sites have nearby sites for SFF (e.g., in FAR1, SPO12, KIN3, and CDC47), although these presumptive SFF sites are of varying quality.…”
Section: The M/g1 Clustersmentioning
confidence: 78%
See 2 more Smart Citations
“…This cluster has similarities to the CLB2 cluster, except that peak expression is slightly later. Searches of the upstream regions reveal that the majority of these genes contain binding sites for Mcm1p, as was previously shown for some members of the cluster (McInerny et al, 1997). Some, but not all, of these MCM1 sites have nearby sites for SFF (e.g., in FAR1, SPO12, KIN3, and CDC47), although these presumptive SFF sites are of varying quality.…”
Section: The M/g1 Clustersmentioning
confidence: 78%
“…Some, but not all, of these MCM1 sites have nearby sites for SFF (e.g., in FAR1, SPO12, KIN3, and CDC47), although these presumptive SFF sites are of varying quality. It has been suggested that some of the genes in this cluster are regulated through the "ECB," a variant of the Mcm1p binding site (McInerny et al, 1997).…”
Section: The M/g1 Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation that we have discovered for PCL9 is unique among known cyclins. The G 1 cyclin CLN3, like PCL9, has peak expression at the M/G 1 boundary but is regulated by the Mcm1 protein rather than Swi5 (McInerny et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The major part of this coordination is achieved by the sequential activation of a small number of transcription regulators (reviewed in Mendenhall and Hodge, 1998): MBF (a complex of Mbp1p and Swi6p) and SBF (a complex of Swi4p and Swi6p) are responsible for activating G1 transcription (Koch et al, 1993); Fkh1p and a complex formed by the cooperative promoter binding of Mcm1p and Fkh2p and a later recruitment of Ndd1p are responsible for activating G2/M transcription (Koranda et al, 2000;Kumar et al, 2000;Pic et al, 2000;Hollenhorst et al, 2001); Swi5p and Ace2p, which are themselves expressed during G2/M, are the transcription factors responsible for activating the greater part of the next wave of M/G1 transcription (Dohrmann et al, 1992;Toyn et al, 1997); and Mcm1p, this time alone, is additionally responsible for activating transcription of several other M/G1 genes (McInerny et al, 1997).…”
Section: Introductionmentioning
confidence: 99%